A meta-analytic review of emotional exhaustion in a sales context. Issue 3 (3rd July 2019) - Edmondson, Diane R.; Matthews, Lucy M.; Ambrose, Scott C.
Abstract: Despite 20 years of empirical study on salesperson burnout, involving dozens of articles, researchers have yet to reach consensus on a common knowledge base. As a result, momentum has waned in recent years without clear guidance on a path forward. Through meta-analytic review, this study seeks to clarify what is known in a sales setting about burnout's central component, emotional exhaustion. The findings will be juxtaposed with findings from similar meta-analytic reviews performed on emotional exhaustion in other work settings. Through this process, research gaps will emerge that can help guide more programmatic research in the future; the results will provide managers with clearer guidance on mitigating burnout.